Bacterial Community Profiles in Tapai Singkong: a Traditional IndonesianFermented Food from Cassava Tubers - Tati Barus; Andiny Ndu Ufi; Watumesa Agustina Tan; Ana Lucia Ekowati; Adi Yulandi (Microbiology Indonesia, 2022)
Tapai singkong is one of the popular fermented foods in Indonesia, which is processed from cassava tubers (Manihot utilissima ). The bacteria present during the fermentation process de Manihot utilissima determines the quality of Tapaisingkong. However, information about the bacteria of Tapai singkong is still limited.Â  Therefore, this study aimed to analyze the bacterial community of based on culturing techniques Tapai singkong and based on metagenomic sequencing with Next-Generation Sequencing (NGS) techniques. Five types of samples were Tapai singkong obtained from producers in Jakarta, Bogor, Tangerang, Band Tapai singkong ung, and Kediri-Indonesia. The bacterial community in this study was studied in from Kediri Tapai singkong because the taste was most favored by the panelists based on the hedonic test. Based on the culture technique using De Man Rogosa and Sharp Agar media, the two most abundant bacterial isolates were found. Based on the 16S rRNA gene sequence, both isolates were the same lactic acid bacteria (LAB), namely Pediococcus acidilactici DSM 20284, with 99.6% similarity. Based on metagenomic sequencing, it was found that the bacteria in the consisted of Firmicutes Tapai singkong (82%), Bacteriodetes (10%), unidentified bacteria (5%), and Verrucomicrobia (1%). The genus of Firmicutes was dominated by the LAB group, namely Pediococcus (61.23%), Weissella (4.8%), Lactobacillus (3.9%), Sporolactobacillus (2.2%), and Staphyloccocus (2.1%). The results of this study showed that the LAB group was most abundant in Tapai singkong . Therefore, the role of each LAB needs to be studied further to determine its role in the quality of Tapai singkong.